2023
DOI: 10.1186/s12909-023-04094-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and comparing critical thinking skills of residents of Tehran University of Medical Sciences

Abstract: Background Today’s complexities and diversity in the clinical setting have revealed the need to pay attention to strengthening critical thinking (CT) skills. The present study aimed to evaluate and compare CT skills in the residents of the Tehran University of Medical Sciences. Methods This is a cross-sectional study. The study's statistical population included 284 residents in orthopedic, internal medicine, and surgery groups studying in the PGY1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…They also found that students were low on the truth-seeking scale due to their reading habits. Another study in Tehran, Iran, found more than 65% of students fell into the weak CT category (Mehrpour et al, 2023). Findings from previous studies indicated that it was necessary to strengthen students' Critical Thinking.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…They also found that students were low on the truth-seeking scale due to their reading habits. Another study in Tehran, Iran, found more than 65% of students fell into the weak CT category (Mehrpour et al, 2023). Findings from previous studies indicated that it was necessary to strengthen students' Critical Thinking.…”
Section: Introductionmentioning
confidence: 96%
“…Critical thinking skills (CT) are essential for learners as they are needed to be more skilful, to identify alternative solutions, to prevent mistakes, and to make the right decisions (Mehrpour et al, 2023). CT is related to achieving students' success in learning while helping them avoid negative life phenomena (Damopolii et al, 2022;Ghanizadeh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Critical thinking is not explicitly included within the ambits of core competency in medical curricula in most cases. 1 , 2 , 5 Now, the time requires that teaching and learning critical thinking skills should be explicitly considered in the curriculum for medical undergraduates. However, critical thinking and its implications in undergraduate medical education suffer from a lack of conceptual clarity.…”
Section: Introductionmentioning
confidence: 99%